2015
DOI: 10.4254/wjh.v7.i12.1701
|View full text |Cite
|
Sign up to set email alerts
|

1H nuclear magnetic resonance spectroscopy-based metabonomic study in patients with cirrhosis and hepatic encephalopathy

Abstract: Patients with cirrhosis and patients with hepatic encephalopathy exhibit distinct metabolic abnormalities and the use of metabonomics can select biomarkers for these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
5
22
0
Order By: Relevance
“…Notably, the three types of HCC tumors were significantly distinguishable by changes in ketone body metabolism with the following associated metabolite profiles: acetoacetate (ALD>HBV>HCV), alanine (ALD and HBV>HCV), and glycerol (ALD>HBV and HCV). Previous plasma metabonomic research has demonstrated that ketone body and ketogenic amino acid levels are significantly increased in cirrhotic patients, suggesting that peripheral ketone body utilization is impaired in cirrhotic patients [ 15 ]. As acetoacetate is the primary ketogenic product [ 15 ], our findings further suggest that ketogenesis is the most pronounced in ALD HCC tumors, followed by HBV-infected HCC tumors, and lastly HCV-infected HCC tumors in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the three types of HCC tumors were significantly distinguishable by changes in ketone body metabolism with the following associated metabolite profiles: acetoacetate (ALD>HBV>HCV), alanine (ALD and HBV>HCV), and glycerol (ALD>HBV and HCV). Previous plasma metabonomic research has demonstrated that ketone body and ketogenic amino acid levels are significantly increased in cirrhotic patients, suggesting that peripheral ketone body utilization is impaired in cirrhotic patients [ 15 ]. As acetoacetate is the primary ketogenic product [ 15 ], our findings further suggest that ketogenesis is the most pronounced in ALD HCC tumors, followed by HBV-infected HCC tumors, and lastly HCV-infected HCC tumors in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous plasma metabonomic research has demonstrated that ketone body and ketogenic amino acid levels are significantly increased in cirrhotic patients, suggesting that peripheral ketone body utilization is impaired in cirrhotic patients [ 15 ]. As acetoacetate is the primary ketogenic product [ 15 ], our findings further suggest that ketogenesis is the most pronounced in ALD HCC tumors, followed by HBV-infected HCC tumors, and lastly HCV-infected HCC tumors in cirrhotic patients. Notably, this hypothesis is further supported by the observed higher glycerol levels in ALD relative to HBV-infected and HCV-infected HCC tumors, suggesting increased triglyceride catabolism and fatty acid oxidation contributing to enhanced ketone body synthesis in ALD HCC tumors in cirrhotic patients [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of pyruvate, which was significantly higher, glycolysis end-products and gluconeogenesis precursors (pyruvate, alanine, threonine, glycine and aspartate) were significantly lower in cirrhotics with encephalopathy than without and both higher than controls. There was no discernable effect of encephalopathy on branched-chain and aromatic amino acids or on urea cycle intermediates [161]. Yet, again, such NMR-derived metabolites do not show sufficient specificity to be considered as biomarkers.…”
Section: Fibrosis and Cirrhosismentioning
confidence: 91%
“…In cirrhosis, hepatic gluconeogenesis is impaired. The amino acid precursors of glucose synthesis, such as alanine, threonine, glycine, and aspartate, are increased, whereas peripheral anaerobic glycolysis increases lactate and pyruvate levels [18]. Of particular importance, studies demonstrate that glycine may be an ammoniagenic amino acid, causing increased ammonia synthesis in the gut and brain through induction of a reaction mediated by glycine oxidase [19].…”
Section: The Role Of Hepatocytes and Endothelial Cellsmentioning
confidence: 99%
“…On the other hand, the low systemic availability of glucose causes hepatocytes to produce more ketone bodies from fatty acids, for the energetic metabolism of nervous and muscular tissues. However, it is hypothesized that in situations like this, hepatocytes prioritize the production of energy for its own subsistence rather than synthesizing products destined for exportation to other tissues [18]. Thus, ketogenesis would also be impaired, which is corroborated by significantly decreased betahydroxybutyrate and acetoacetate levels, resulting in a precarious energy metabolism in the central nervous system in the advanced stages of the disease [18,21].…”
Section: The Role Of Hepatocytes and Endothelial Cellsmentioning
confidence: 99%